Drying studies of oyster mushroom - ATHIRA P BINITHA V. PAI; Dr. Santhi Mary Mathew (Guide) (Tavanur 2007 Kelappaji college of Agricultural Engineering and Technology)
Drying studies of oyster mushroom
Drying studies of oyster mushroom